Targeting parvalbumin-expressing neurons in the substantia nigra pars reticulata restores motor function in parkinsonian mice - Lorena Delgado-Zabalza; Nicolas P. Mallet; Christelle Glangetas; Guillaume Dabee; Maurice Garret; Cristina Miguelez; Jérôme Baufreton (Cell Reports, 2023)
Summary: The activity of substantia nigra pars reticulata (SNr) neurons, the main output structure of basal ganglia, is altered in Parkinson’s disease (PD). However, neither the underlying mechanisms nor the type of neurons responsible for PD-related motor dysfunctions have been elucidated yet. Here, we show that parvalbumin-expressing SNr neurons (SNr-PV+) occupy dorsolateral parts and possess specific electrophysiological properties compared with other SNr cells. We also report that only SNr-PV+ neurons’ intrinsic excitability is reduced by downregulation of sodium leak channels in a PD mouse model. Interestingly, in anesthetized parkinsonian mice in vivo, SNr-PV+ neurons display a bursty pattern of activity dependent on glutamatergic tone. Finally, we demonstrate that chemogenetic inhibition of SNr-PV+ neurons is sufficient to alleviate motor impairments in parkinsonian mice. Overall, our findings establish cell-type-specific dysfunction in experimental parkinsonism in the SNr and provide a potential cellular therapeutic target to alleviate motor symptoms in PD.